TEACHER'S PERCEPTION OF ENGLISH LEARNING FOR CHILDHOOD - Nurul Fatonah (Prodi. Pendidikan Islam Anak Usia Dini, Institut Pesantren KH. Abdul Chalim, 2021)
This research will investigate about teacher’s perception of English learning for childhood. This research is conducted in four kindergartens in Garut with the teacher as the subject. This research aims in digging teacher’s perception of the English learning. This research will use phenomenology research with descriptive interpretation towards English learning phenomenon. In this phenomenology research, the researcher describes nature based experience. The data were collected by interview, observation, and note of the field. Then the data were analyzed through the steps of phenomenology data analysis. The result showed that English is a necessary for Indonesian society. It happens because of globalization claim. In the application, English learning that has been done in kindergarten through song, greeting, or simple instruction and environment labeling by English language.